Customer relationship management: is it still relevant to commercial banks in Taiwan? - Yao, Hui-I; Khong, Kok Wei (Canadian Center of Science and Education, 2012)
Nowadays, customers are regarded as a commodity. Customer Relationship Management (CRM) in a bank entails important phases such as integrating the communication tools to meet the needs of customers, treating each customer as individuals, and making the customer relationship an imposing and perpetual experience. The aim of this research is to determine the effectiveness of CRM implementation on customer satisfaction and perceived business performance. Literature suggests that successful CRM efforts involve proper deployment of the three phases in CRM implementation, i.e. acquisition, enhancement and recovery phases. Furthermore, there is a strong causal relationship between CRM implementation and customer satisfaction as well as perceived business performance. A survey was carried out using a survey instrument on commercial banks in Taiwan. Findings revealed that CRM implementation is positively associated with customer satisfaction and perceived business performance as suggested by the literature. Contact rate and recovery management were found to be associated with customer retention while acquisition management, regular contact and evaluation of customers lead to improved loyalty and employee sentiments. In a managerial point of view, this study provides an outline of the impact of CRM efforts on the dimensions of customer satisfaction and perceived business performance.